Disputes over the reasons for Sweden's economic success: Nima Sanandaji and his critics - Bogusław Czarny (International Journal of Management and Economics, 2021)
I analyze selected views of the well-known Swedish analyst of Nordic economies, Nima Sanandaji, on the reasons for the economic (and social) successes of Sweden and other Nordic countries in the 20th and 21st centuries. My aim is not to provide a detailed and full appraisal of these views but to confront them with the arguments of Sanandaji's critics. Only occasionally do I supplement the arguments of Sanandaji's commentators with additional comments of my own. In particular, my interests include the following theses of Sanandaji: the thesis that Sweden's prosperity arose before the development of the welfare state, which contributed little to its creation; the thesis that other Swedish successes (health, small inequalities, equal opportunities) are wrongly attributed to the Swedish welfare state or are far from complete; the thesis that there is very limited scope for other countries to copy the Swedish (Nordic) experience. In the Conclusion, I comment on the reception of Sanandaji's views in Poland.
Keywords: N14; O11; O52; 650; economic history of Sweden; Nordic model; Sweden